Prevalence of Candida dubliniensis Isolates in a Yeast Stock Collection - Odds, Frank C. (American Society for Microbiology, 1998)
To establish the historical prevalence of the novel yeast species Candida dubliniensis, a survey of 2,589 yeasts originally identified as Candida albicans and maintained in a stock collection dating back to the early 1970s was undertaken. A total of 590 yeasts, including 93 (18.5%) β-glucosidase-negative isolates among 502 isolates that showed abnormal colony colors on a differential chromogenic agar and 497 other isolates, were subjected to DNA fingerprinting with the moderately repetitive sequence Ca3. On this basis, 53 yeasts were reidentified as C. dubliniensis (including the C. dubliniensis type strain, included as a blind control in the panel of yeasts). The 52 newly found isolates came from 36 different persons, and a further 3 C. dubliniensis isolates were detected by DNA fingerprinting of previously untested isolates from one of these individuals. The prevalence of C. dubliniensis among yeasts in oral and fecal samples was significantly higher than that among yeasts from other anatomical sites and was significantly higher among human immunodeficiency virus (HIV)-infected individuals than among known or presumed HIV-negative individuals. However, a single vaginal isolate and two oral isolates from healthy volunteers confirmed that the species is restricted neither to gastrointestinal sites nor to patients with overt disease. The oldest examples of C. dubliniensis were from oral samples of three patients in the United Kingdom in 1973 and 1975. In comparison with age-matched control isolates of C. albicans, the C. dubliniensis isolates showed slightly higher levels of susceptibility in vitro to amphotericin B and flucytosine and slightly lower levels of susceptibility to three azole antifungal agents.